A Bottom Sediment Distribution Map for the Portuguese Continental Shelf in ArcGis Format: Mapa da Distribuição de Sedimentos Superficiais da Plataforma Continental Portuguesa em Formato ArcGis - Silva, A.J.F. (2015)
This work presents a simplified map of the spatial distribution of surficial sediments and rock outcrops along the Portuguese continental shelf in ArcGIS format. Preliminary map preparation involved scanning, georeferencing and digitizing of pre-existing base maps from the Portuguese Hydrographic Institute and harmonization with other published and non-published cartographic information. Samples of soft bottom shelf sediments from nearly 500 sites, collected in the scope of the MeshAtlantic, RENSUB and ACOSHELF projects, were analyzed for grain-size and total organic matter. Grain-size analysis was performed using dry and wet sieving. The procedure includes chemical destruction of organic matter with H2O2, chemical dispersion with tetra-sodium pyrophosphate, separation of the mud fraction by wet sieving and dry sieving of both sand and gravel fractions. Raw grain-size data were expressed as weight percentages and classified according to a modified version of the Folk classification system. Grain size data for the whole set of samples were used to create a new sediment distribution map and develop an easy-to-use GIS interface, that will be available in the MeshAtlantic website, as part of a global broadscale habitat map for the Atlantic Area. Overall, the bottom sediment distribution patterns show that: (a) the coarser deposits occur mainly in the inner and mid-shelf of the northwestern sector of the Portuguese shelf, to the south of the Nazaré and Setúbal canyons, and are sparsely represented in the southern shelf; (b) sand banks dominate in the near shore shelf, but can sporadically be found at greater depths; (c) muddy sands characterize the deeper shelf; (d) patches of sandy mud and mud reflecting a less energetic hydrodynamic regime cover a large sector of the southern shelf and areas located off the mouths of major rivers in the western shelf; (e) mixed sediments are residual; (f) rock outcrops are unevenly distributed throughout the entire shelf.